Implementation of Outdoor Learning Methods in Improving Student Learning Outcomes in Islamic Religious Education Subjects at MAN 1 Medan - Zulfirman, Rony; Gunawan (Edumaniora : Jurnal Pendidikan dan Humaniora, 2022)
Formal education systems often face challenges associated with monotonous and rigid learning processes, which prioritize standardization over individual creativity. This research aims to address these issues by exploring the implementation of outdoor learning methods as a means to enhance student learning outcomes. Focusing specifically on Islamic Religious Education subjects at MAN 1 Medan, the study seeks to investigate the planning, execution, monitoring, and evaluation of outdoor learning methodologies. By adopting an outdoor learning approach, this research endeavors to introduce a more dynamic and experiential learning environment, breaking away from the constraints of traditional indoor pedagogy. Through observation, interviews, and documentation, the study assesses the effectiveness of outdoor learning methods in stimulating student engagement, fostering critical thinking skills, and enhancing overall learning outcomes. The findings of this research contribute valuable insights into the potential benefits of outdoor learning approaches in formal education settings. By offering an alternative to conventional classroom-based instruction, outdoor learning methodologies have the potential to promote creativity, curiosity, and active participation among students, thereby enriching their educational experiences and improving academic performance.